Hans Gerhard Creutzfeldt (1885–1964) in the Third Reich: A reevaluation. (14th July 2020) - Illert, Michael; Schmidt, Mathias
Abstract : Hans Gerhard Creutzfeldt (1885–1964) is an internationally known Professor of Psychiatry and Neurology. During the time of National Socialism (1933–1945), he worked in the Charite University Hospital Berlin and moved to Kiel University as Head of the Department for Psychiatry and Neurology in 1938. Until the turn of the millennium, Creutzfeldt was considered to be of moral integrity and an opponent of the Nazi regime and its eugenics measures. Publications of the last years came to the conclusion that this depiction does not hold up. They questioned his relations to the ideas and structures of the National Socialist system, his role as a consultant in the National Socialist's forced sterilization program, a possible involvement in the Nazi euthanasia measures, and his position as a psychiatric consultant for the German navy. The article considers 2 aspects concerning the National Socialist racial hygiene in greater detail by using newly found source material. It is shown that Creutzfeldt, although he did not actively resist, was not acting in the interest of the Nazi regime, but rather was trying to save as much patients as possible by changing their diagnoses and prevent them from being killed in the euthanasia program.